Optimization of tillage and fertilizers for productive and profitable sunflower in paddy fallows of deep Vertisols of Karnataka: Optimization of tillage and fertilizers for productive and profitable sunflower in paddy fallows of deep Vertisols of Karnataka - M R UMESH; U K SHANWAD; VIKAS V KULKARNI; N ANANDA; N VIJAYKUMAR; GHANTE; POORNIMA; Y M RAMESH (Journal of Oilseeds Research, 2020)
Study was conducted on deep Vertisols to evaluate the influence of tillage and fertilizer levels on performance of sunflower hybrids in paddy fallows. Sunflower hybrids were grown in conventional-till (CT), Minimum-till (MT), Reduced-till (RT) and zero-till (ZT) with graded fertilization. Averaged across fertilizer rates, cultivars, and years, sunflower seed yields were greater with CT (1477 kg/ha) than with MT, RT and ZT. Graded fertilizers at 150% RDF (1424 kg/ha) increased grain yield over RDF and reduced level at 75% RDF but varied over years. Economic returns also higher in CT along with graded fertilizers for RSFH-1887. Results indicate sunflower can be grown successfully in paddy fallows with CT and MT and graded fertilization in the Vertisols.